Sosialisasi Bank Sampah dan Pemanfaatan Limbah Menjadi Produk Bernilai di Desa Cibatu sebagai Pengembangan Desa Go Green - Sakum; MH Ainulyaqien; Yudianto Achmad; Adam Lubis; Saiful Mukti Ali (DPPM Universitas Pelita Bangsa, 2021)
Environmental issues are problems that cause damage to the habitat of living things. It is largely caused by human social and economic activities aimed at fulfilling life's needs. One simple effort that can be made to reduce household waste is to separate organic and inorganic waste. Organic waste can be composted, while inorganic waste can be turned into various recycled products. This is done through the waste bank programme. In the community service programme, there are several methods of approach that can help in solving existing problems. One of them is through training, counselling, and guidance methods, so that residents/communities can understand waste management and utilise it into goods that have economic value. The Community Service Team (PKM) carried out this method in three stages, namely preparation, socialisation, and mentoring. In the preparation stage, researchers discussed the waste condition in the village, waste management programmes, and socialisation of waste banks. There is a need to understand the dangers of waste to the environment and health. The ability to manage household waste has a significant impact on various aspects of life. Socialisation activities regarding the utilisation of beverage wrapper waste into useful items through handicraft making videos from household waste. In dealing with the waste problem, socialisation activities involving the utilisation of beverage wrap waste into handicrafts have an important role.